KESALAHAN BERBAHASA TATARAN MORFOLOGI DALAM TEKS AKADEMIK MAHASISWA ASING UNIVERSITAS JAMBI - Aprilia, Silvy; Wibowo, R. Imam Suwardi; Rahmawati, Rahmawati; Priyanto, Priyanto (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the form of morphological level errors in scientific texts of foreign students at the Indonesian Language and Literature Education Study Programme, Faculty of Teacher Training and Education, Jambi University. This research uses a qualitative research type using a content analysis approach. The data of this study were obtained by giving assignments to foreign students in the form of papers (as the main data) and interviews with foreign students from Thailand (as supporting data). The data were analyzed qualitatively with a content analysis approach. The results of this study show that the forms of language errors at the morphological level that are often encountered are basic word formation errors, morph replacement, improper use of affixes, omission of affixes, and reduplication errors. The obstacles faced by foreign students in writing academic texts, namely differences in sentence structure, lack of mastery of vocabulary in Indonesian, still influenced by Malay language, and difficulties in word formation and addition of affixes.